Evidence of small microplastics (<100 μm) ingestion by Pacific oysters (Crassostrea gigas): A novel method of extraction, purification, and analysis using Micro-FTIR. (November 2020) - Corami, F.; Rosso, B.; Roman, M.; Picone, M.; Gambaro, A.; Barbante, C.
Abstract: Microplastics (MPs) are present in fresh, brackish, or marine waters. Micro- and macroinvertebrates can mistake MPs or small microplastics (SMPs, <100 μm) to be food particles and easily ingest them according to the size of their mouthparts. SMPs may then block the passage of food through the intestinal tract (i.e. hepatopancreas), accumulate within the organism, and enter the food web. Pacific oysters ( Crassostrea gigas ) are allochthonous filter-feeding bivalve mollusks, which have been introduced in coastal seas around the world in both natural banks and farms. Considering their economic and ecological value, these bivalves have been chosen as a model to study the ingestion of SMPs. A novel method for the extraction and purification of SMPs in bivalves was developed. Quantification and simultaneous polymer identification of SMPs using Micro-FTIR (Fourier Transform Infrared Spectroscopy) were performed, with a limit of detection for the particle size of 5 μm. Graphical abstract: Unlabelled Image Highlights: New methods developed for gills and hepatopancreas of Crassostrea gigas Quantification and identification of small microplastics (<100 μm) using Micro-FTIR Quantification and identification of additives and natural fibers using Micro-FTIR